HUBUNGAN INTENSITAS PENGGUNAAN GAWAI TERHADAP KETERLAMBATAN PERKEMBANGAN PADA ANAK USIA 3-5 TAHUN DI KECAMATAN CINERE TAHUN 2020 - Martalia Ayu Purnamasari, (2020)
Background. Gadget is one of the most used technologies among adults and children. During the golden period, it is very important to provide stimulation that can stimulate the child's development. Aspects of the development in children includes aspects of rough motor, fine motor, speech and language, as well as socialization and independence. Purpose. The study aims to determine whether there is a relationship between the intensity of gadget use towards the development delay in 3-5 years old children in Kecamatan Cinere. Method. This study uses cross sectional design. The subject of this study was 3-5 years old children who went to kindergarten in Kecamatan Cinere. This study uses a purposive sampling technique with a sample size 76 subjects. Data obtained using a intensity of gadget use questionnaire and KPSP. Result. Based on the results of data analysis found 53.95% of female children, 71.05% of children aged 54-60 months, 56.58% of children's parents education is S1, 56.58% of parents' job are housewives. The results of bivariate analysis using chi square showed that there was a low and significant relationship between the intensity of gadget use and the development delay in 3 - 5 years old children in kindergarden at Kecamatan Cinere (p-value = 0.005). Among the four aspects of development, aspect of speech and language that are most influenced by the intensify of gadget use (coefficient correlation = 0.400). Conclusion. There is a relationship between the intensity of gadget use towards the development delay in 3 - 5 years old children in cinere district. Key words : delay, gadget, intensity, children development